2009
DOI: 10.1089/end.2008.0230
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endoscopic Management Versus Open Revision of Ureteroenteric Anastomotic Strictures After Urinary Diversion—Single Institution Contemporary Series

Abstract: Endoscopic management continues to have success rates that remain lower than that of open revision. Left-sided strictures remain more common than right-sided strictures; however, side and stricture length were not found to be statistically significant in our series. The lack of consistent postoperative functional renal studies highlights the importance of diligent monitoring and warrants further study to develop a surveillance algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…This is consistent with previous series by Laven et al [15] and Milhoua et al [14] who reported success rates of 80 and 87.5%, respectively. These data suggest that open revision remains the gold standard for treatment of ureteroeneteric anastomotic strictures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous series by Laven et al [15] and Milhoua et al [14] who reported success rates of 80 and 87.5%, respectively. These data suggest that open revision remains the gold standard for treatment of ureteroeneteric anastomotic strictures.…”
Section: Discussionsupporting
confidence: 93%
“…Laven et al [13] reported success rates of 57% with endoureterotomy applying the holmium laser. Milhoua et al [14] reported a 27% success rate using a variety of endoscopic strategies including balloon dilation, electrosurgical incision, and incision with the holmium laser. Lower success rates in the present series could be related to several factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, with longer follow-up duration, the success rate drops to 71.4-80% 6,9,[49][50][51] ; in the study with longest follow-up duration (a median of 47 months), Nassar et al 6 reported a success rate of 78% in 32 patients. This low rate of success with longer follow-up duration might be the result of an increased number of contemporary open repairs performed in patients in whom primary endoscopic interventions have failed.…”
Section: Open Repairmentioning
confidence: 96%
“…Although the exact etiology remains unclear, they most likely occur secondary to ischemia after interruption of ureteral blood supply during surgery or impaired healing due to radiotherapy [5]. Open surgical revision of the ureteroileal anastomosis and ureter re-implantation remains the gold standard with long-term success rates ranging from 76 to 92% [6,7]. However, this may prove to be technically challenging due to the formation of fibrotic adhesions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of conventional ureteral stents are infection, bleeding, irritative symptoms, encrustation, and stone formation, all leading to a reduced quality of life [9]. Repetitive high pressure dilation with angioplasty balloon and cold cut procedures have been reported to have long-term success rates of 16 and 51%, respectively [7,10]. Therefore, long-term segmental thermo-expandable metallic stents were introduced to alleviate lower urinary tract symptoms and avoid the need for regular exchange.…”
Section: Introductionmentioning
confidence: 99%